Exploring the role of students' views of creativity on feeling creative. Issue 1 (2nd January 2022) - Rani Satyam, V.; Savić, Miloš; Cilli-Turner, Emily; El Turkey, Houssein; Karakok, Gulden
Abstract : Creativity is crucial for doing mathematics, yet many United States students may not have opportunities to experience it in their courses. Moreover, the literature base on views of mathematical creativity lacks the student perspective. To explore the connections between views of and feeling creative, we examine differences in views of creativity between students who felt creative and did not feel creative in an interventional Calculus I course. We conducted semi-structured interviews with 37 undergraduate students taking a creativity-based Calculus I course across the United States, for their views on creativity and whether they felt creative in the course. Approximately three quarters felt creative ( n  = 27), while one quarter of students ( n  = 10) did not. Using qualitative coding, we found that students who did not feel creative were more likely to view creativity as including understanding and applications . In contrast, students who felt creative were more likely to view creativity as originality and actions and attitudes they could take. We recommend instructors take actions focusing on originality and actions and attitudes to help foster students' creativity. Finally, we discuss how all ten students who did not feel creative came from groups that have been historically marginalized in mathematics.